New Psychoactive Substances: the Surprise Guest in Clinical and Therapeutic Approaches - Beyamina, A (Emerging trends in drugs, addictions, and health, 2024)
Pharmacological identification and screening is one data point among many when approaching patients with polysubstance use disorders. This information must be completed with detailed clinical observations of subjects who use them in order to determine the potential dangers and adverse effects of NPS. NPS are used by a wide variety of persons from all walks of life. Their reasons for using, their expectations from the drug, their perceived satisfaction, and benefits from the substance as well as the adverse events and risks are key to repeating the experience. An individual's context is also key: how they obtain the substance and how they administer it and how often. These elements are not necessarily dependent on the pharmacological properties of the substance. NPS users are frequently polydrug users. The cumulative toxicity with other more habitual substances may present the greatest dangers to consumers. In this context, blanket legislation banning all potential psychoactive substances may encourage producers to more widespread innovation with potentially greater risks to users. Such legislation may actually prevent us from gaining access to clinically relevant data to make appropriate benefit-risk analyses of NPS. Encouraging efforts to support early warning systems, to rapidly identify upticks in overdoses and toxicity, remain important in our risk reduction efforts to consumers.